The Correlation of Dietary Habit with Incidence of Gastritis - Ade Fitriani; Ajeng Silvia Nurislami; Lilis Lismayanti; Nur Hidayat (Inspirasi Foundation, 2022)
Objective: The purpose of this study was to determine the relationship between diet and the incidence of gastritis in adolescents at Madrasah Aliyah Negeri 2 Ciamis (MAN 2 Ciamis), Ciamis Regency, West Java. Method: The research desain used in this study is an analytical survey, to find the relationship between diet and the incidence of gastritis in adolescents, it is carried out with a cross sectional approach. The population used in this study were all teenagers consisting of class X students with a total population of 62 people. The total sample used is 56 people. The sampling technique used is purposive sampling, which is the sampling of data sources with the consideration of 56 respondents. To find the relationship between the two variables, the SPSS TEST was used to obtain the results of the chi-square test with a 95% confidence level and presented in the form of tables and narratives. Result: In this study, as many as (67.9%) adolescents with poor dietary habits experienced more gastritis than those who did not experience gastritis (32.1%) and The results of the non-parametric chi square test showed a large number of values = 0.000 < 0.05 which stated that there was a significant relationship between diet and the incidence of gastritis in adolescents. Conclusion: There is relationship between dietary habits and the incidence of gastritis in adolescents at MAN 2 CIAMIS.